2023
DOI: 10.5603/cj.a2021.0064
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor effectively inhibits platelet aggregation in comatose survivors of cardiac arrest undergoing primary percutaneous coronary intervention treated with mild therapeutic hypothermia

Abstract: Background: Mild therapeutic hypothermia (MTH) is believed to reduce the effectiveness of antiplatelet drugs. Effective dual-antiplatelet therapy after percutaneous coronary intervention (PCI) is mandatory to avoid acute stent thrombosis (ST). The effectiveness of ticagrelor in MTH-treated out-of-hospital cardiac arrest (OHCA) survivors is still a matter of debate. The aim of the study was to evaluate the impact of MTH on the platelet-inhibitory effect of ticagrelor in comatose survivors of OHCA treated with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…Tomala et al [32] reported similar findings for a time range of 12-24 hours, however in this team's observation the difference disappeared 48-72 hours after loading. This finding led the authors to a conclusion quite different from one reached by Tomala et al [33] and Umińska et al [34]. The analysis of the methods and results of both studies shows, however, that despite different conclusions, both studies are consistent, and moreover, they complement each other.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Tomala et al [32] reported similar findings for a time range of 12-24 hours, however in this team's observation the difference disappeared 48-72 hours after loading. This finding led the authors to a conclusion quite different from one reached by Tomala et al [33] and Umińska et al [34]. The analysis of the methods and results of both studies shows, however, that despite different conclusions, both studies are consistent, and moreover, they complement each other.…”
mentioning
confidence: 73%
“…Recently, two pharmacokinetic studies with seemingly contradictory conclusions appeared in the “Cardiology Journal”. First, Tomala et al [ 33 ] confirms the effectiveness of ticagrelor to inhibit platelets in MI patients after OHCA treated with pPCI undergoing hypothermia. The other, by Umińska et al [ 34 ], states that the antiplatelet effect of ticagrelor is attenuated and delayed in MI patients undergoing MTH and pPCI due to OHCA, in comparison with patients treated with pPCI for uncomplicated MI.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Due to its rapid onset of action cangrelor appears to be the optimal P2Y12 receptor inhibitor for ACS patients requiring urgent invasive treatment [44,45]. This compound may be considered in patients not pre-treated with oral P2Y12 receptor inhibitors at the time of PCI or in those who are considered unable to absorb oral agents, particularly in unconscious patients, patients with post-cardiac arrest syndrome, or patients treated with mild therapeutic hypothermia, when gastrointestinal absorption of medications is impaired [2,5,[46][47][48]. Unfortunately, up to date cangrelor is not available in Poland.…”
Section: Platelet P2y12 Receptor Inhibitorsmentioning
confidence: 99%
“…The PERSEUS study, however, does not provide a comparison with any non-opioid treatment strategy, making it impossible to truly assess the effects of fentanyl on the pharmacokinetics and pharmacodynamics of ticagrelor in AMI patients. In this specific clinical setting, despite opioid-induced decreased bioavailability of P2Y12 receptor inhibitors, some additional factors, including enhanced platelet activation and reduced gastrointestinal perfusion as well as impact of mild therapeutic hypothermia applied in cardiac arrest survivors, may also impede the effect of oral antiplatelet drugs [18][19][20][21][22][23][24].…”
mentioning
confidence: 99%